Sex and N-terminal pro B-type natriuretic peptide: The potential mediating role of iron biomarkers - Khatami, Farnaz; Muka, Taulant; Groothof, Dion; de Borst, Martin H.; Buttia, Chepkoech; van Hassel, Gaston; Baumgartner, Iris; Kremer, Daan; Bakker, Stephan J. L.; Bano, Arjola; Eisenga, Michele F. (Frontiers in Cardiovascular Medicine, 2022)
Background Levels of N-terminal pro B-type natriuretic peptide (NT-proBNP), a marker of heart failure and cardiovascular risk, are generally higher in women than men. We explored whether iron biomarkers mediate sex differences in NT-proBNP levels. Methods We included 5,343 community-dwelling individuals from the Prevention of Renal and Vascular Endstage Disease study. With linear regression analyses, we investigated the association of sex and iron biomarkers with NT-proBNP levels, independent of adjustment for potential confounders. The assessed iron biomarkers included ferritin, transferrin saturation (TSAT), hepcidin, and soluble transferrin receptor (sTfR). Next, we performed mediation analyses to investigate to which extent iron biomarkers influence the association between sex and NT-proBNP. Results Of the included 5,343 participants, the mean standard deviation age was 52.2±11.6 years and 52% were females. After adjustment for potential confounders, women compared to men, had higher NT-proBNP (β= 0.31; 95%CI= 0.29, 0.34), but lower ferritin (β= -0.37; 95%CI= -0.39, -0.35), hepcidin (β= -0.22, 95%CI= -0.24, -0.20), and TSAT (β= -0.07, 95% CI= -0.08, -0.06). Lower ferritin (β= -0.05, 95%CI= -0.08, -0.02), lower hepcidin (β= -0.04, 95%CI= -0.07, -0.006), and higher TSAT (β= 0.07; 95%CI= 0.01, 0.13) were associated with higher NT-proBNP. In mediation analyses, ferritin and hepcidin explained 6.5% and 3.1% of the association between sex and NT-proBNP, respectively, while TSAT minimally suppressed (1.9%) this association. Conclusions Our findings suggest that iron biomarkers marginally explain sex differences in levels of NT-proBNP. Future studies are needed to explore causality and potential mechanisms underlying these pathways.